2023
DOI: 10.14338/ijpt-22-00022.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Ultra-hypofractionated Proton versus Photon Therapy in Extremity Soft Tissue Sarcoma

Abstract: Purpose Recent single institution, phase II evidence has demonstrated the feasibility and efficacy of ultra-hypofractionated, preoperative photon therapy in 5 fractions for the treatment of soft tissue sarcoma (STS). Our purpose was to evaluate the dosimetric benefits of modern scanning beam proton therapy compared with conventional photon radiation therapy (RT) for the neoadjuvant treatment of adult extremity STS. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…These studies reported the safety and efficacy of this approach and established the currently advised planning margins that would be used in this case—specifically, 3 to 4 cm superiorly/inferiorly and 1.5 cm radially, cropping the clinical target volume extending beyond the muscular compartment and including the suspicious edema and guided by the use of CT-based planning fused with T1 postcontrast and T2 MRI sequences to delineate the tumor volume 15 . Nonetheless, in the aforementioned IGRT trials, wound healing and/or acute toxicity complication profiles were generally similar to those of earlier approaches; techniques to improve toxicity profiles through dose-reduction are thus being pursued 20,21 . The standard, conventional preoperative dose in this case would be 1.8 to 2 Gy in 25 to 28 daily (weekday) fractions of external beam radiation (Fig.…”
Section: Team Approachmentioning
confidence: 94%
“…These studies reported the safety and efficacy of this approach and established the currently advised planning margins that would be used in this case—specifically, 3 to 4 cm superiorly/inferiorly and 1.5 cm radially, cropping the clinical target volume extending beyond the muscular compartment and including the suspicious edema and guided by the use of CT-based planning fused with T1 postcontrast and T2 MRI sequences to delineate the tumor volume 15 . Nonetheless, in the aforementioned IGRT trials, wound healing and/or acute toxicity complication profiles were generally similar to those of earlier approaches; techniques to improve toxicity profiles through dose-reduction are thus being pursued 20,21 . The standard, conventional preoperative dose in this case would be 1.8 to 2 Gy in 25 to 28 daily (weekday) fractions of external beam radiation (Fig.…”
Section: Team Approachmentioning
confidence: 94%
“…To explore this potential risk, our group conducted a dosimetric analysis, comparing target coverage and dose to surrounding organs at risk when treating extremity STS with identical hypofractionated regimens of photon and proton radiation as those which will be used in this trial [ 26 ]. Doses to skin were statistically similar between the two modalities for most of the dosimetric endpoints outside of mean and maximum doses, which were slightly lower with PBT than photon RT.…”
Section: Introductionmentioning
confidence: 99%
“…To explore this potential risk, our group conducted a dosimetric analysis, comparing target coverage and dose to surrounding organs at risk when treating extremity STS with identical hypofractionated regimens of photon and proton radiation as those which will be used in this trial (25). Doses to skin were statistically similar between the two modalities for most of the dosimetric endpoints outside of mean and maximum doses, which were slightly lower with PBT than photon RT.…”
Section: Introductionmentioning
confidence: 99%
“…As shown, the target receives similar coverage in the two plans, while the normal tissue outside of the target receives lower doses in the proton plan. Figure adopted from study by Thomas et al (25).…”
Section: Introductionmentioning
confidence: 99%